Induction of a bZIP Type Transcription Factor and Amino Acid Catabolism-Related Genes in Soybean Seedling in Response to Starvation Stress. (10th November 2013) - Yuasa, Takashi; Nagasawa, Yuri; Osanai, Katsumasa; Kaneko, Ayami; Tajima, Daichi; Htwe, Nang Myint Phyu Sin; Ishibashi, Yushi; Iwaya-Inoue, Mari
Abstract : To address roles of bZIP transcription factors on regulation of amino acid catabolism under autophagy-induced plant cells, we examined the effect of nutrient starvation on the expression of low energy stress-related transcription factor homologs, GmbZIP53A and GmbZIP53B, and amino acid catabolism-related genes in soybean ( Glycine max (L.) Merr.). Sucrose starvation treatment significantly enhanced the expressions of GmbZIP53A, but not GmbZIP53B asparagine synthase ( GmASN1 ), proline dehydrogenase1 ( GmProDH ), and branched chain amino acid transaminase 3 ( GmBCAT3 ). GmbZIP53-related immunoreactive signals were upregulated under severe starvation with sucrose starvation and protease inhibitors, while 3% sucrose and sucrose starvation had no or marginal effects on the signal. Profiles of induction of GmASN1, GmProDH and GmBCAT3 under various nutrient conditions were consistent with the profiles of GmbZIP53 protein levels but not with those of GmbZIP mRNA levels. These results indicate that GmbZIP53 proteins levels are regulated by posttranslational mechanism in response to severe starvation stress and that the increased protein of GmbZIP53 under severe starvation accelerates transcriptional induction of GmASN1, GmProDH, and GmBCAT3 . Furthermore, it is conceivable that decrease of branched chain amino acid level by the BCAT-mediated degradation eventually enhances autophagy under severe starvation.